Socio-cultural, organizational factor and career development of female employees: A study on school teachers - Maharjan, Sarita (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
The main objective of this study is to examine the impact of socio-cultural and organizational factors affecting the career development of female employees. With judgmental/ purposive sampling technique, only 142 respondents have been selected out of 150 questionnaires distributed to female school teachers. This study has tested reliability of questionnaires by using Cronbach alpha. Using multiple regression analysis, it has been found that both socio-cultural and organizational factors have negative impact on women career development. Hence, a conclusion can be drawn-out of the study that there are negative impacts of socio-cultural and organizational factors on women career development. Considering the outcomes, it can be claimed that the study could be useful for school management, trainers, and human resource developers to assist the career development of female school teachers.